Impact of a multi-step testing algorithm on hospital-onset Clostridioides difficile rates and clinical outcomes - Matthew A. Moffa; Dustin R. Carr; Nathan R. Shively; Adriana Betancourth; Nitin Bhanot; Zaw Min; Charmaine Abalos; Arshpal Gill; Salman Bangash; Thomas L. Walsh (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract